Indonesia Corporate Governance Manual, Second Edition - International Finance Corporation (Washington, DC, 2018)
The Indonesia Corporate Governance Manual discusses key corporate governance elements that have been contextualized to take into account current Indonesian laws and regulations as well as international best practices. While it is recommended to read the entire Manual to gain a full understanding of the corporate governance framework in Indonesia, it is not necessary to read all the chapters in chronological order. The Manual includes examples, illustrations, and checklists to aid clarity and understanding.